Analysis of Handling of Student Complaints about Open University Services : Study at UT Kupang (Universitas Terbuka, 2023)
The purpose of this study was to identify and analyze the behavior of Open University students as consumers related to service complaints within UT Kupang. This study aims to identify and analyze: (1) the quality of complaint handling services at UT Kupang in terms of student behavior and level of satisfaction as consumers; (2) What things need to be done by UT Kupang to increase the speed of service for complaints submitted by students as consumers. The data used in this research is primary data. Primary data was obtained by distributing questionnaires to respondents according to a predetermined sample. the average value of the quality of complaint handling services at UT Kupang seen from students' perceptions is in the appropriate/very high category. But overall, UT students still perceive the quality of complaint handling services at UT Kupang to be poor, because the complaint handling services received or in fact are lower than what students expect. To improve complaint handling services at UT Kupang, all aspects need improvement because they have a negative average gap value.